Strategi Internalisasi Nilai-Nilai Anti Radikalisme pada Peserta Didik Madrasah Tsanawiyah - Sya’roni, Muhammad; Muna, Nailil (CENDEKIA, 2023)
Radicalism continues to spread through various media until now. Schools must protect students from the radical ideology influence. Psychologically, the age of MTs students is teenagers. Teenagers are a vulnerable, unstable, and immature age so they are influenced by many things, including religious radicalism. One of the school's efforts to prevent students from radicalism is the internalization of anti-radicalism values. This research aims to explain the strategies adopted by MTs Islamiyah Tulungagung Baureno in internalizing anti-radicalism values in students and the anti-radicalism values that are internalized. Through analysis of interview data, observation, and documentation, it was found the strategies pursued by MTs Islamiyah as follows: Integration in Learning Materials; Integration in the Learning Process; Integration in Religious Habituation Activities; Integration in School Routine Activities, Modeling, and Spotless Actions. The anti-radicalism values that are integrated through these various activities are faith and devotion, love of the country, compassion, courtesy, justice, moderation, respect for others, self-control, tolerance, mutual cooperation, mutual help, and cooperation.